(untitled) (Economics and region, 2022)
In the article the problem of introduction of innovations into the economy of Ukraine is investigated and the influence of globalization on these processes is determined, the positive consequences of this phenomenon for the national economy as a whole are highlighted, because it is the way to create a high-tech, competitive state with a developed economy. The key principles of formation and directions of increasing the innovativeness of the national economy are determined. The analysis of the state policy on the legislative framework that regulates and stimulates the introduction and development of innovations at the state and interstate levels is carried out, the priorities of innovation implementation are determined. The necessity of creating favorable conditions and implementing appropriate mechanisms of state policy to promote the restoration and development of the national economy on an innovative basis, integrated into the world community, is substantiated. Globalization is the basis of economic interconnection of countries and is determined by the deepening of international economic relations and the creation of a system of global, interregional and regional organizations. Foreign economic relations in the world economy create the growth of all relations: trade and investment, labor and information, social. In economic terms, globalization is manifested in the strengthening of the role of supranational integration and openness of national economies, the conclusion of economic agreements at the regional and global level, the growing influence of transnational corporations, the global division of labor, the smooth functioning of the world economic mechanism and the rapid response of financial markets to world events. Globalization gives Ukraine an opportunity to build a developed market competitive economy based on innovations and implementation of innovative management methods. This will create positive changes for the restoration and stabilization of economic processes in Ukraine, provide additional opportunities for the development of the national economy, which is impossible without investment inflows from economically developed partner countries, create a favorable environment for rapid integration into the world economy.